Methodology for Assessing Transport Connections on the Integrated Transport Network - Jozef Gasparik; Vladimir Luptak; Petr V. Kurenkov; Pavol Mesko (Communications - Scientific letters of the University of Zilina, 2017)
The periodic line transport expresses an integrated periodic timetable, which is also a periodical liner form of surveillance and network interconnection. An important factor is to reduce the interchange times in selected areas, or transport hubs. The aim is to minimise the total transit time of a passenger from point A to point B. The cornerstone of transport services is to provide travel opportunities by creating links and connections. Often, after the introduction of the new timetable and a discussion of whether it is better or worse, each approach is evaluated in a subjective manner. The authors solved some problems of rail passenger quality services. At present, there is no methodology for assessing train timetables from the transportation point of view as a whole. We evaluate specific trains and connections in the stations only, but not the quality of the connection from point A to point B.